The Highly Conserved Asp23 Family Protein YqhY Plays a Role in Lipid Biosynthesis in Bacillus subtilis - Tödter, Dominik; Gunka, Katrin; Stülke, Jörg (Frontiers in Microbiology, 2017)
In most bacteria, fatty acid biosynthesis is an essential process that must be controlled by the availability of precursors and by the needs of cell division. So far, no mechanisms controlling synthesis of malonyl coenzyme A, the committed step in fatty acid synthesis, have been identified in the Gram-positive model bacterium Bacillus subtilis. We have studied the localization and function of two highly expressed proteins of unknown function, YqhY and YloU. Both proteins are members of the conserved and widespread Asp23 family. While the deletion of yloU had no effect, loss of the yqhY gene induced the rapid acquisition of suppressor mutations. The vast majority of these mutations affect subunits of the acetyl-CoA carboxylase (ACCase) complex, the enzyme that catalyzes the formation of malonyl-CoA. Moreover, lack of yqhY is accompanied by the formation of lipophilic clusters in the polar regions of the cells indicating an increased activity of ACCase. Our results suggest that YqhY controls the activity of ACCase and that this control results in inhibition of ACCase activity. Hyperactivity of the enzyme complex in the absence of YqhY does then provoke mutations that cause reduced ACCase activity.